A presença da angústia em um conto de Mia Couto - Biziak, Jacob dos Santos [UNESP] (2014)
This article intends an approach among literary analysis, philosophy and psichoanalysis in a short story from Mia Couto, Mozambican author. From the trajectory of the main character and from their relationship with the others, we intended to do a reading on the presence of anguish within this literary text. In order to do that, two definitions were used to explain what would be considered torment: one from the philosopher Kierkegaard and the other from the psichoanalyst Freud. Concluding, we aim to compare this two readings in a way that we establish bounds between both.